2020
DOI: 10.1002/ange.202004364
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Biscognienyne B Involving a Cytochrome P450‐Dependent Alkynylation

Abstract: The alkyne is a biologically significant moiety found in many natural products and a versatile functional group widely used in modern chemistry. Recent studies have revealed the biosynthesis of acetylenic bonds in fatty acids and amino acids. However, the molecular basis for the alkynyl moiety in acetylenic prenyl chains occurring in a number of meroterpenoids remains obscure. Here, we identify the biosynthetic gene cluster and characterize the biosynthetic pathway of an acetylenic meroterpenoid biscognienyne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…9A ). 22 Particularly, they found that the alkyne in 28 was installed by the cytochrome P450 enzyme BisI, which is different from the other reported enzymes dedicated to acetylenic bond biosynthesis. In order to explore the mechanism and substrate scope of the BisI-mediated biosynthesis of the alkynyl moiety, the authors chemically prepared the 1-OH methylated form ( 31 ) of 4-hydroxy-3-prenylbenzoic acid and performed feeding experiments ( Fig.…”
Section: Biosynthesis Of Acetylenic Natural Productsmentioning
confidence: 69%
See 2 more Smart Citations
“…9A ). 22 Particularly, they found that the alkyne in 28 was installed by the cytochrome P450 enzyme BisI, which is different from the other reported enzymes dedicated to acetylenic bond biosynthesis. In order to explore the mechanism and substrate scope of the BisI-mediated biosynthesis of the alkynyl moiety, the authors chemically prepared the 1-OH methylated form ( 31 ) of 4-hydroxy-3-prenylbenzoic acid and performed feeding experiments ( Fig.…”
Section: Biosynthesis Of Acetylenic Natural Productsmentioning
confidence: 69%
“… 74,75 Recently, two research groups simultaneously reported that the alkynyl moieties in the prenyl chains of biscognienyne B ( 28 ) and asperpentyn ( 29 ) are generated by cytochrome P450 enzymes, as determined via heterologous expression, feeding experiments and in vitro enzyme reactions. 22,23 Furthermore, the two groups demonstrated that the stereochemistry of the double bond in the intermediates is important for substrate recognition.…”
Section: Biosynthesis Of Acetylenic Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterologous expression, feeding experiments, and in vitro assays were used to characterize the biosynthetic pathway. Specifically, an novel cytochrome P450-dependent BisI was shown to be involved in alkynylation of the prenyl chain (Lv et al 2020) (Fig. S11).…”
Section: Meroterpenoid With Unique Structuresmentioning
confidence: 99%